Inhibitors of Mitogen-Activated Protein Kinases Downregulate COX-2 Expression in Human Chondrocytes - Nieminen, Riina (Hindawi Publishing Corporation, 2005)
Inducible prostaglandin synthase (cyclooxygenase-2, COX-2) is expressed in rheumatoid and osteoarthritic cartilage and produces high amounts of proinflammatory prostanoids in the joint. In the present study we investigated the effects of the inhibitors of mitogen-activated protein kinase (MAPK) pathways Erk1/2, p38, and JNK on COX-2 expression and prostaglandin E(2) (PGE(2)) production in human chondrocytes. Proinflammatory cytokine IL-1β caused a transient activation of Erk1/2, p38, and JNK in immortalized human T/C28a2 chondrocytes and that was followed by enhanced COX-2 expression and PGE(2) production. PD98059 (an inhibitor of Erk1/2 pathway) suppressed IL-1-induced COX-2 expression and PGE(2) production in a dose-dependent manner, and seemed to have an inhibitory effect on COX-2 activity. SB203580 (an inhibitor of p38 pathway) but not its negative control compound SB202474 inhibited COX-2 protein and mRNA expression and subsequent PGE(2) synthesis at micromolar drug concentrations. SP600125 (a recently developed JNK inhibitor) but not its negative control compound N(1)-methyl-1,9-pyrazolanthrone downregulated COX-2 expression and PGE(2) formation in a dose-dependent manner. SP600125 did not downregulate IL-1-induced COX-2 mRNA expression when measured 2 h after addition of IL-1β but suppressed mRNA levels in the later time points suggesting post-transcriptional regulation. Our results suggest that activation of Erk1/2, p38, and JNK pathways belongs to the signaling cascades that mediate the upregulation of COX-2 expression and PGE(2) production in human chondrocytes exposed to proinflammatory cytokine IL-1β.